Network Perspective In The Internationalization Of Indonesian SMEs In The Era Of Indutrial Revolution 4.0 - Anni Yudiastuti; F. Danardana Murwani; Sudarmiatin; Agus Hermawan (International Journal of Science, Technology & Management, 2021)
The level of globalization that goes hand in hand with the 4.0 industrial revolution demands the fighting power of companies both in large and small and medium scales to determine dynamic strategies in anticipating competition and expansion targets through international markets. SMEs in Indonesia as the spearhead and pillars of Indonesia's economic strength are also required to be able to improve their performance, especially in promoting their business on an international scale. Indonesian product SMEs for export competitiveness are mostly based on local wisdom-based products, therefore innovation is needed in developing products with local wisdom. Various obstacles faced by SMEs in managing their businesses, especially related to limitations in implementing production management activities, human resource management and marketing management. The solution to the various limitations that have become problems for SMEs in facing the internationalization process is to establish a network that involves various stakeholders. The networkQuality and integrated with the support of government programs will be able to support the competence and capabilities of SMEs in facing the internationalization process in the industrial revolution 4.0. This study examines the role of networks in enhancing the internationalization strategy of Indonesian SMEs.